Outcome of mini percutaneous nephrolithotomy ‘miniPCNL’ in children (Journal of Patan Academy of Health Sciences, 2018)
Introductions: Renal stone disease is one of the common urological disorders with prevalence approximately 2-3% in the general population and the incidence in children is increasing at a rate of 4% per year. Miniaturization of endoscopic instruments, minimally invasive endoscopic procedures of mini percutaneous nephrolithotomy (miniPCNL) in children is increasingly used. This study was conducted to assess the outcome of miniPCNL in pediatric population.Methods: This retrospective study analyzed the outcome of miniPCNL in children below 18 years of age from August 2015 to July 2018 at Patan Hospital, Nepal. Ethical approval was obtained. Outcome was assessed descriptively on stone localization, puncture success, stone clearance, bleeding requiring transfusion, gross hematuria, urosepsis, operative time, hospital stay, mortality and need of second procedures.Results: A total of 26 patients underwent miniPCNL, mean age 10.8±5.45 years (1-18 years), mean operative time was 122±26.03 minutes and mean hospital stay was 3.2±1.12 days.  Postoperative transfusion was required in 1 (2.6%), gross hematuria occurred in 1 (2.6%), no urosepsis, no conversion to open surgery. Complete stone clearance was achieved in 22 (84.61%) patients.  Mortality was nil. Second procedure was required in 4 (15.38%) to achieve residual stone clearance.Conclusions: Our study shows miniPCNL is an effective and safe procedure with minimal morbidity for the treatment of pediatric renal stones.